2006
DOI: 10.1096/fj.05-5622fje
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative mitogenic signaling by G protein‐coupled receptors and growth factors is dependent on Gq/11

Abstract: Previously we reported that the G protein-coupled receptor (GPCR) agonist thrombin potentiated the mitogenic effect of epidermal growth factor (EGF) on human airway smooth muscle (ASM) by promoting sustained late-phase activation of PI3K and p70S6K via a pathway dependent on Gbetagamma subunits of heterotrimeric G proteins. Here, we provide additional mechanistic insight and reveal the robustness of this phenomenon by demonstrating that H1 histamine and thromboxane receptors utilize the same mechanism to augme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 44 publications
5
57
0
Order By: Relevance
“…6). Previous studies have demonstrated that p70S6 kinase is a critical effector of mitogenic signaling mediated by receptor tyrosine kinases, GPCRs, and PI3K in ASM (3,29,32). As previously demonstrated, PDGF and EGF stimulation resulted in increased activation of p70S6 kinase.…”
Section: Tas2r Agonist-mediated Antimitogenic Effect Does Not Involvesupporting
confidence: 51%
See 1 more Smart Citation
“…6). Previous studies have demonstrated that p70S6 kinase is a critical effector of mitogenic signaling mediated by receptor tyrosine kinases, GPCRs, and PI3K in ASM (3,29,32). As previously demonstrated, PDGF and EGF stimulation resulted in increased activation of p70S6 kinase.…”
Section: Tas2r Agonist-mediated Antimitogenic Effect Does Not Involvesupporting
confidence: 51%
“…Stable expression of green fluorescent protein (GFP), protein kinase A inhibitory peptide (PKI)-GFP, and RevAB-GFP was achieved by retroviral infection, as described previously (15,20,29,55). Briefly, retrovirus for the expression of each was produced by cotransfecting GP2-293 cells with pVSV-G vector (encoding the pantropic VSV-G envelope protein) and either pLNCX2-GFP, or pLNCX2-PKI-GFP, and viral particles were harvested from supernatant.…”
Section: Methodsmentioning
confidence: 99%
“…In human airway smooth muscle cells, various GPCR agonists, which are often weak mitogens themselves, have been shown to promote the synergistic stimulation of cell proliferation when combined with growth factors such as EGF www.nature.com/aps Xie KQ et al Acta Pharmacologica Sinica npg or platelet-derived growth factor (PDGF) [9] . Previous reports have shown that the GPCR agonist thrombin can potentiate the mitogenic effects of EGF in human airway smooth muscle [10] . EGFR has been recognized as a convergence point for diverse signal transduction pathways [11] .…”
Section: Introductionmentioning
confidence: 93%
“…Activation of the G i -coupled pathway reduces cAMP and thus indirectly promotes contractility. Although much of the previous work in this area has focused on expression and function of different GPCRs (typically G q , G i , and G s ) in the context of ASM contractility/relaxation, there is increasing recognition that GPCRs acting alone, or in conjunction with other pathways such as receptor tyrosine kinases (18,20,59,155,162), can contribute to the "synthetic function" of ASM via cell proliferation/growth and secretion of growth factors and inflammatory mediators, thus influencing airway remodeling and the local inflammatory milieu (e.g., see Refs. 20 and 59 for review).…”
Section: Asm [Ca 2ϩ ] I and Contractilitymentioning
confidence: 99%
“…However, there is also some suggestion that "normal" stimuli such as bronchoconstrictor agonists (114,233,341) and other locally produced factors (5,53,75) could trigger increased proliferation under certain conditions, leading to the asthmatic phenotype. In this regard, interactions between GPCRs and RTKs may be important (18,67,68,155,162,303). For example, M 2 muscarinic receptors can potentiate TGF-␤-induced enhancement of proliferation (216).…”
Section: Asm In Airway Remodelingmentioning
confidence: 99%